The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1109/tcad.2006.887920
|View full text |Cite
|
Sign up to set email alerts
|

Performance Benefits of Monolithically Stacked 3-D FPGA

Abstract: Abstract-The performance benefits of a monolithically stacked three-dimensional (3-D) field-programmable gate array (FPGA), whereby the programming overhead of an FPGA is stacked on top of a standard CMOS layer containing logic blocks (LBs) and interconnects, are investigated. A Virtex-II-style two-dimensional (2-D) FPGA fabric is used as a baseline architecture to quantify the relative improvements in logic density, delay, and power consumption achieved by such a 3-D FPGA. It is assumed that only the switch t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(77 citation statements)
references
References 29 publications
2
73
0
2
Order By: Relevance
“…If 3D integration technology is introduced in the future to stack several mrFPGAs together, at least two more times of improvements in density and speedup, i.e. 10x and 4.5x respectively, are both expected, according to the experimental results on 3D architecture in [17].…”
Section: B Evaluation Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…If 3D integration technology is introduced in the future to stack several mrFPGAs together, at least two more times of improvements in density and speedup, i.e. 10x and 4.5x respectively, are both expected, according to the experimental results on 3D architecture in [17].…”
Section: B Evaluation Resultsmentioning
confidence: 98%
“…A 3D FPGA architecture was proposed in [17]. It partitions the transistors in the routing structure and logic structure of conventional FPGA into multiple active layers and stacks the layers via monolithic stacking, a 3D integration technology the author proposes to use as shown in Fig.…”
Section: B Recent Work On Fpgas Using Emerging Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach requires monolithic 3D integration because of the high density of inter-layer via required. The study in [6] has shown that such stacking cans achieve3.2 times higher logic density, 1.7 times lower delay, and 1.7 times lower dynamic power consumption than a baseline2D-FPGA implemented in 65nm CMOS technology. These improvements are achieved with appropriate optimization of buffer and transistor sizes, but without any change to the FPGA architecture.…”
Section: C) Programming Overhead Stackingmentioning
confidence: 99%
“…Renewed interest in 3D device packaging has direct applicability to FPGA logic [140] and routing structures [139]. As transistor channel widths shrink deep into the submicron realm, the manufacturability of reliable FPGA routing becomes an issue.…”
Section: Challenges In Basic Routing Architecturementioning
confidence: 99%